Robust control of railway traction electric drive systems in terms of energy efficiency - İlhan Mutlu; Dincel, Emre; Canevi, Mehmet; M. Turan Söylemez (Zenodo, 2018)
In this study, firstly, the model of railway traction electric drive systems is derived analytically along with the indirect vector control approach. In such systems, there are several disturbance and uncertainty sources like varying total weight, weight distribution, environmental conditions, voltage irregularities etc. Furthermore, resistive forces that is based on curve and grade topology, tunnel effects, velocity and aerodynamics of trains directly affects the motion control problem. In order to overcome such difficulties, a new robust pole placement approach is proposed for the speed control of such systems considering the total resistive forces, the possible uncertainties that may occur. The proposed approach is based on affine linear polynomials and D-stability. A conversion is also possible from PID type controllers to PI-PD cascade controller structure in order to eliminate the effects of undesired open loop zeros. Using the proposed approach, it becomes possible to guarantee certain predetermined performance criteria corresponding to a robust performance with energy efficiency. Additionally, correctness and effectiveness of the derived theoretical results are verified via a case study.
Keywords: Railway traction systems; induction motor control; robust control; robust pole placement; low order controller design